1997
DOI: 10.1002/(sici)1099-0968(199703)5:1<11::aid-erv179>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Children of Mothers with Eating Disorders: A Preliminary Study

Abstract: This study investigated the extent of psychiatric disorder and abnormalities of weight and growth amongst children of mothers with eating disorders. The design was a cross-sectional study, in which mothers were identi®ed by attendance at specialist eating disorder services. Assessments included interviews with the mothers and children, questionnaires included EAT and child behaviour questionnaires (Rutter A scale), and weight and height of mothers and children was measured. Thirteen mothers who had 26 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
4
24
1
Order By: Relevance
“…Throughout the history of mental illness, it has been determined that psychiatric disorders in parents have a detrimental effect on their children (Stein 1995, Rutter & Quinton 1984 and it has been established that children of mothers with an eating disorder are at greater risk of developing the illness themselves (Stein et al 2006, Hodes et al 1997, Stein 1995, Sourfield 1995, Stein et al 1993. As early as 1860, Louis Victor Marce noticed that inherited psychopathologies were prominent in families of young women with what was yet to be diagnosed as anorexia nervosa (Strober & Bulik 2002).…”
Section: Heritabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Throughout the history of mental illness, it has been determined that psychiatric disorders in parents have a detrimental effect on their children (Stein 1995, Rutter & Quinton 1984 and it has been established that children of mothers with an eating disorder are at greater risk of developing the illness themselves (Stein et al 2006, Hodes et al 1997, Stein 1995, Sourfield 1995, Stein et al 1993. As early as 1860, Louis Victor Marce noticed that inherited psychopathologies were prominent in families of young women with what was yet to be diagnosed as anorexia nervosa (Strober & Bulik 2002).…”
Section: Heritabilitysupporting
confidence: 92%
“…I will discuss later in this study the evidence that has established that the children of eating disordered mothers are at greater risk of developing the disorders themselves (Stein et al 2006, Park et al 2003, Hodes et al 1997, Stein 1995, Sourfield 1995, Stein et al 1993. It is understood by observation and research into child development that all children grow and develop by watching and mirroring their mother or main care giver (Kohut 1984, Winnicott 1960, so it seems evident that if the mother is lacking in her own autonomous states and her behaviour is overtly dysfunctional, that the child will internalise and eventually display this behaviour.…”
Section: To Conduct a Group Interventionmentioning
confidence: 99%
“…Past investigations have proposed that the offspring of women with BN may be at risk of becoming obese; 315,343 findings from the present study showed that boys of women from all exposed groups had higher adiposity than boys of unexposed women, with the difference being more pronounced at the age of 5 years. Taking into consideration that boys of mothers with other psychiatric problems have similar BMI trajectories to those of unexposed mothers, the differences we found in growth trajectories in the offspring of mothers with EDs may be specific to maternal eating pathology.…”
Section: Gender Differencesmentioning
confidence: 84%
“…Furthermore, these results are similar to previous case studies and those with younger children that show that children of women with AN do not grow as much as those of unexposed women. 321,343,345 Past research has shown that mothers with an ED are more concerned with their daughters' weight and shape than with their sons', 346 and that their daughters may have a higher chance of becoming underweight than thier sons. 343 Results from the current studies support gender-specific growth trajectories; however, as our growth models were built separately for each gender, we were unable to examine gender interactions.…”
Section: Gender Differencesmentioning
confidence: 98%
“…It is becoming widely recognized that the children of eating disordered mothers are at high risk of developing an eating disorder themselves (Stein et al, 1994;Scourfield, 1995;Stein, 1995;Hodes et al, 1997;Van der Broucke et al, 1997;Agras, et al, 1999;Waugh and Bulik, 1999). The risk factors not only point to a genetic vulnerability (Holland et al, 1988;Strober, 1991;Stunkard, 1995;Lilenfield et al, 1998;Collier et al, 1999;Graber et al, 1999;Strober and Bulik, 2002) but also to environmental factors.…”
Section: Riskmentioning
confidence: 99%